Human Condition in Kazuo Ishiguro’s Never Let Me Go (Philologia, 2021)
The purpose of this paper is to highlight, through a comprehensive psychological and sociological analysis of characters in Kazuo Ishiguro’s novel Never Let Me Go, how roles, rules, habits, and routines, imposed either externally or internally, ultimately take the better of us, making our lives empty and superficial. Ishiguro’s characters – parentless clones with a “higher” purpose in life, stand as perfect examples of how easy it is to forget what human existence is all about, how easy it is to sink into the bottomless sea of human tragedy, or, as Ishiguro himself once put it – “the sadness of the human condition”. The paper utilizes john Dewey’s Human Nature and Conduct, and the so-called “role theory”, to argue social role versus private life, passivity and suppression of feelings, while trying to provide answers to the key questions: why don’t the clones rebel and why can’t they be human.
Keywords: social roles; habits; passivity; repression; imitation of life; rebellion; human(ity); suppression of feelings